Albania : Eighth Review Under the Extended Arrangement and Request for Modification of Performance Criteria-Press Release and Staff Report. (IMF Staff Country Reports; Country Report, 2016)
This paper discusses Albania's Eighth Review Under the Extended Arrangement and Request for Modification of Performance Criteria . All performance criteria at the end of April 2016 were met with comfortable margins, and good progress has been made on the structural reform agenda. The economic recovery is strengthening, supported by large energy-related investments and a gradual recovery in domestic demand. The current account deficit is widening owing to import-intensive foreign direct investment. Inflation is recovering from very low levels, although underlying inflation pressure remains weak. The IMF staff supports the completion of the Eighth Review under the Extended Arrangement.